Interatrial block in prediction of all-cause mortality after first-ever ischemic stroke - M. A. Baturova; A. Lindgren; Y. V. Shubik; J. Carlson; P. G. Platonov (BMC Cardiovascular Disorders, 2019)
Abstract Background Interatrial block (IAB) is an ECG indicator of atrial fibrosis related to atrial remodeling and thrombus formation thus leading to embolic stroke and increasing mortality. We aimed to assess weather IAB predicted all-cause mortality during 10 years after ischemic stroke. Methods The study sample comprised 235 patients (median age 74 (interquartile range 25–75% 65–81) years, 95 female) included in the Lund Stroke Register in 2001–2002, who had sinus rhythm ECGs at stroke admission. IAB was defined as a P-wave duration ≥120 ms without = partial IAB (n = 56) or with = advanced IAB (n = 41) biphasic morphology (±) in the inferior ECG leads. All-cause mortality was assessed via linkage with the Swedish Causes of Death Register. Results During follow-up 126 patients died (54%). Advanced IAB, but not partial, was associated with all-cause mortality in univariate Cox regression analysis (hazard ratio (HR) 1.98, 95% CI 1.27–3.09, p = 0.003). After adjustment for age, gender, severity of stroke measured by NIHSS scale and smoking status in patients without additional comorbidities advanced IAB independently predicted all-cause mortality (HR 7.89, 95% CI 2.01–30.98, p = 0.003), while in patients with comorbidities it did not (HR 1.01 95% CI 0.59–1.72, p = 0.966). Conclusion Advanced IAB predicted all-cause mortality after ischemic stroke, but mostly in patients without additional cardiovascular comorbidities.